Indonesia Stock Exchange: What Affects the Dividend Policy on Mining Companies? - Widi Hidayat, Nirma Kusumaningrum, (Opción, 2020)
Mining companies have a major influence on Indonesia's economic growth so that good capital management is needed regarding investment. Dividend policy is a problem that often debated by shareholders and the company because it is considered to signal the company's financial condition. This study analyzed factors (Cash Ratio, Debt to Equity Ratio, Return of Asset and Firm Size) that influence dividend policy in mining companies in Indonesia. Cash ratio and Debt to Equity Ratio were partially tested against negative dividend policies which were not significant (p>0.05) while Return on Assets and Firm Size partially showed significant (p<0.05).